Some results of full-scale experiments to study the effect of forest fires on atmospheric characteristics - Loboda, Egor L.; Kasymov, Denis P.; Agafontsev, Mikhail V.; Reyno, Vladimir V.; Lutsenko, Anastasia V.; Martynov, Pavel S.; Golubnichiy, Egor N.; Orlov, Konstantin E.; Staroseltseva, Asya A.; Arshinov, M. Yu; Loboda, Yuliya A.; Gordeev, E. V. (Proceedings of SPIE)
The article presents the results of a series of mesoscale experiments to study wildfires and their impact on the atmosphere. A change in meteorological parameters, a significant increase in fluctuations of the refractive index, speed of sound and temperature in the vicinity of the experiment, which are a reflection of the occurrence of turbulent processes in the atmosphere, were established, experimental data were obtained on changes in the concentration of methane and carbon dioxide as a result of a fire, and data were obtained on the mechanism of occurrence of crown fire.